Multimorbidity patterns and function among adults in low- and middle-income countries: a scoping review - Karina Berner; Quinette A Louw; Eugene Nizeyimana; Diribsa Tsegaye Bedada (BMJ Open)
Objectives To map the scope of available evidence on relationships between multimorbidity patterns and functioning among adults in low- and middle-income countries (LMICs), and describe methods used.Design Scoping review guided by a five-step methodological framework and Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews reporting guidelines.Data sources PubMed/MEDLINE, Scopus, EBSCOhost (CINAHL) and Cochrane databases were searched from January 1976 to March 2023, plus reference lists of included studies.Eligibility criteria for selecting studies Peer-reviewed full-text articles or conference proceedings of any design, published in English or Afrikaans, involving adults (>18 years) with multimorbidity living in LMICs. Studies had to refer to associations between multimorbid patterns of co-occurrence and functioning. Multimorbidity was defined as the coexistence of ≥2 diseases, including any combination of non-communicable, infectious and mental health conditions.Data extraction and synthesis Data were extracted independently by two reviewers using a piloted form. Findings were synthesised according to methodological approaches, multimorbidity-pattern epidemiology, evidence gaps/limitations and recommendations for future research. The International Classification of Functioning, Disability and Health framework was used to classify functional problems.Results Nine studies (total sample size: 62 003) were included, mainly from upper-middle-income Asian countries. Key methodological inconsistencies were identified in defining and operationalising multimorbidity, conditions included in determining patterns, statistical methods for pattern determination and functioning outcome measures. Five main multimorbidity pattern domains emerged: Cardio-Metabolic and Coronary Atherosclerotic, Musculoskeletal, Respiratory and Digestive/Visceral, Degenerative, and Mental Health-Related. Mobility limitations, instrumental activities of daily living, self-care and bowel/bladder problems were consistently linked to all pattern domains.Conclusions The limited and geographically skewed body of literature, along with methodological inconsistencies, hampers a comprehensive understanding of multimorbidity patterns and associations with functioning in LMICs. Future research should explore context-specific multimorbidity definitions, employ transparent methodologies, use standardised measures and incorporate diverse samples to inform tailored interventions and policies.